SUSTAINABLE DEVELOPMENT AND ARCHITECTURE: ECONOMIC FEASIBILITY OF DUALISTIC CONSTRUCTION - YASHCHENKO, Oleksii; MAKATORA, Dmytro; KUBANOV, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The characteristics, principles, and directions of sustainable development in architecture have been identified. The economic feasibility of implementing sustainable development in architecture has been substantiated. The Fourth Industrial Revolution has been considered in the context of sustainable development. The authors suggest utilising the latest technologies and innovations to enhance production efficiency, reduce emissions through the implementation of clean technologies, and utilise resources rationally. By combining the opportunities presented by the Fourth Industrial Revolution with sustainable development approaches, it is possible to achieve a balance between economic, social, and environmental aspects of development. Sustainable architecture aims to minimise negative environmental impacts and improve building performance by consuming fewer resources, reducing waste, and creating a functional and productive environment. The text discusses the importance of sustainable principles in architecture, including adaptability of architecture, recycling of resources, use of sustainable and renewable materials, and energy efficiency. The economic feasibility of applying sustainable principles in design has also been considered and justified. Additionally, the text provides examples of innovative architectural designs. This is a crucial step towards implementing sustainable building practices. The adaptability of architecture enhances space efficiency by enabling areas to serve various functions based on user requirements. Resource recycling minimises waste and the expense of extracting new materials. The use of sustainable and renewable materials aids in reducing the ecological impact of construction. Energy efficiency helps to decrease energy consumption and GHG emissions. Further research and innovative architectural designs can accelerate the development of sustainable construction and promote its wider adoption in the future. The authors suggest that taking into account the costs of building, maintaining, and operating buildings, as well as a balanced cost-benefit ratio, can significantly influence decision-making in the design and construction process. The authors argue that implementing environmental solutions in architecture may raise the initial project cost. However, in the long run, it can lead to significant economic benefits by reducing energy and maintenance costs, as well as increasing the overall value of the building.
Keywords: economic feasibility; sustainability; architecture; Fourth Industrial Revolution; sustainable building principles; efficiency